PENATALAKSANAAN FISIOTERAPI PADA KONDISI TUBERKULOSIS PARU DENGAN MODALITAS INFRARED DAN ACTIVE CYCLE OF BREATHING TECHNIQUE (ACBT) DI BBKPM SURAKARTA - Ade Rachma Safira; Ade Irma Nahdliyyah (Pena Jurnal Ilmu Pengetahuan Dan Teknologi, 2017)
Tuberculosis is an infectious disease and transmitted directly or indirectly caused byMycobacterium tuberculosa transmitted through the air when a tuberculosis patient coughs andspray saliva containing the bacteria are inhaled by another person while breathing and through thesaliva of using camp today eat / drink The same as the sufferer. This bacteria is an aerobic bacteriacapable of diprik living that has high oxygen partial pressure. Problems that occur in patients withpulmonary tuberculosis yaituseperti cough with phlegm, wheezing, shortness of breath, breathing,decreased thorkas cage and decreased functional activity.Management of physiotherapy in thecondition of pulmonary tuberculosis can be administered by using the modality infrared and activebreathing techniques active (ACBT). The research method used by the writer is using case study.After treatment was 5 times the results (1) decrease the breath of T1: 3 to T5: 0, (2) decrease insputum of T1: ++ (ronkhi loud voice) into T5: + (sound ronkhi downhill), (3 ) decrease in musclespasm of T1 results: 1 (no spasm) into T5: 0 (no spasm), (4) an increase in the expansion of thethoracic cage, (5) an increased functional activity.From the results already obtained, it can beconcluded that physiotherapy treatment on the condition of pulmonary tuberculosis by usinginfrared modalities and active cycle of breathing techniques (ACBT) can help reduce problemsarising on the condition of pulmonary tuberculosis.